Relation of Accumulated Sediment with Coral Reef Cover in the Lagoi Waters Bintan Regency Kepulauan Riau Province - Sidabalok, Westy Yulia; Rifardi, Rifardi; Elizal, Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in Lagoi Waters Banyan Tree Bintan Region to observe effect accumulated sediment on coral. Three stations were selected forthe measurement of accumulated sediment was conducted using sediment traps which is apllied in the station of coral observation for 21 days. Point Intercept Transect (PIT) was used for the observation of coral reef. Regression analyses was applied clarify the correlation between accumulated sediment and coral reef. The result of this study showed that the rate of accumulated sediment in all observation stations ranged from 1.49 – 2.90 mg/cm2/day. The effect can be categorized as low to medium. The condition of coral reef in Lagoi Waters Banyan Tree Bintan Region is classified in good, indicated by percentage of coral cover in observation stations ranged between 50-74%. The result of regression analysis showed that the accumulated has negative impact of life coral reef in Lagoi Waters Banyan Tree Bintan Region.Keywords : Accumulated sediment, Coral reef, Lagoi Waters.